Contested Ideologies of Space in Hispanic American Cartographic Practices: From the Abstract to the Real in Spanish and Indigenous Maps of Yucatán - Barteet, Cody (RACAR : Revue d'art canadienne / Canadian Art Review, 2013)
This paper examines the processes through which early modern cartographers created conflicting spaces of Hispanic America in their respective engagements with monarchial inquiries of Philip II and his successors, and through other judicial proceedings. I primarily analyze cartographic objects produced by the Maya peoples of Yucatán and other indigenous Americans. The cartographs reflect their creators’ heterogeneity, many of whom had differing economic, judicial, and political motivations, that did not always correspond directly to royal interest. Diversity in form and content emerges from this heterogeneity resulting in the formation of new knowledge precepts. By engaging with current academic theories and concepts pertaining to Hispanic American cartography and mapmaking practices, I further consider and advance the supposition that cartographs offer an important glimpse into the formation of Hispanic American culture as well as to the evolution of the map as an abstract form.